P.199 Variability descriptors of cerebral blood flow velocity as predictors of vasospasm in Subarachnoid Hemorrhage: A feasibility study. (November 2021) - Rodriguez, RA; Herry, C; English, S; Ramsay, T; Seely, A; Kenny, GP; Hogan, M; Meade, R; Shamy, M
Abstract : Background: Transcranial Doppler (TCD) measurements poorly predict vasospasm in patients with aneurysmal subarachnoid hemorrhage (aSAH). Variability descriptors of mean cerebral blood flow velocity (mean-CBFV) may improve this prediction. We assessed the feasibility of generating reliable mean-CBFV variability metrics using extended TCD recordings in aSAH patients and healthy controls. We also explored whether these parameters are capable to discriminate aSAH patients from healthy controls, and between patients with and without vasospasm. Methods: Bilateral mean-CBFV, systemic blood pressure and heart rate were recorded for 40 minutes in 3 groups: aSAH patients (n=8) within the first 5 days post-ictus, age-matched healthy controls (n=8) and young healthy controls (n=8). We obtained linear [standard deviations, coefficient of variations, very-low, low and high-frequency power-spectra] and non-linear [Fractality, deterministic Chaos analyses] variability metrics. Results: All TCD recordings provided consistent variability metrics. aSAH patients showed higher correlation dimensions, increased high-frequency spectral power, and decreased very-low frequency power than healthy controls. aSAH patients who developed vasospasm (n=3) showed higher mean-CBFV and lower coefficient of variations than those without vasospasm (n=5). Conclusions: Descriptors of mean-CBFV variability may distinguish between aSAH patients with and without vasospasm. Future studies are required to evaluate the role of these variability parameters for risk stratification in aSAH.